Proposing carbon reduction strategies for mega-urban agglomerations − a cluster analysis based on carbon emission intensity - Cheng, Changgao; Yan, Xiang; Fang, Zhou; Zhou, Qin; Tang, Yan; Li, Nan; Tang, Deshan (Ecological indicators, 2024)
[Display omitted] •Probing heterogeneity of CE in mega-urban clusters via new economic geography.•Construction of vector Kaya expansion model based on urban–rural dual structure.•Unifying analysis of production-side and domestic-side carbon emissions.•Framework for stepwise low-carbon policy in mega-urban agglomerations. Identifying the causes of heterogeneity in carbon emission (CE) performance among different units of a mega-urban agglomeration is crucial for its low-carbon development. This study examines the impacts of regional industrial transformation, living consumption, and spatial expansion on CE using an extended Kaya identity model, focusing on 26 Yangtze River Delta (YRD) cities from 2006 to 2019. Our study reveals that: (1) The development disparities across YRD cities result in distinct CE reduction trajectories, with advanced urban centers showcasing more effective emission control strategies. (2) Living consumption is the primary driver of CE increases, contributing significantly to the rise with a proportion of 137.2%. This is moderated by industrial transformation, which has implemented efficiency improvements and technological innovations to reduce emissions, contributing to a decrease in CE by 48.9%. Spatial expansion also plays a role, accounting for an 11.7% increase in CE. (3) The YRD’s CE reduction efforts are primarily concentrated in core cities, manifesting a pronounced core-periphery structure that includes spillover effects into transitional and peripheral cities. We propose targeted strategies, including incentivizing green technology in high-emission sectors, developing comprehensive low-carbon public transportation, and encouraging sustainable consumer behaviors through education and incentives. These strategies aim for a balanced advancement in industrial practices, urban planning, and public engagement, providing a roadmap for crafting sustainable urban development strategies in similar global contexts.